Survival Analysis of 4 Different Age Groups of Pancreatic Ductal Adenocarcinoma After Radical Resection From Retrospective Multi‐Center Analysis (YPB‐003) - Hiroto Matsui; Tatsuya Ioka; Toru Kawaoka; Tsuyoshi Takahashi; Toshihiro Inokuchi; Eijiro Harada; Kazuhiko Sakamoto; Ryuichiro Suto; Yoshinari Maeda; Taku Nishimura; Yoshitaro Shindo; Yukio Tokumitsu; et al. (Cancer Medicine)
ABSTRACT Aim This study aimed to investigate the efficacy of radical resection and postoperative adjuvant chemotherapy on the survival benefit in patients with pancreatic ductal adenocarcinoma (PDAC), stratified by age, frailty, and other factors in actual clinical practice. Methods We retrospectively analyzed the clinicopathological and follow‐up data of 414 patients with PDAC who underwent surgical resection at nine institutions under the Yamaguchi Pancreat/Biliary Disease Study Group, between January 1997 and December 2016. Recurrence‐free survival (RFS) and overall survival (OS) were calculated using the Kaplan–Meier method. Associations between survival and prognostic factors were evaluated by univariate and multivariate analyses. Results There were 30.5% of patients with PDAC who were aged < 65 years, 37.9% aged 65–74 years, 17.6% aged 75–79 years, and 14.0% aged ≥ 80 years. Notably, RFS declined with increasing age (median RFS: 12.9, 10.2, 9.4, and 7.4 months, respectively), although the differences were not significant (p = 0.223). OS significantly decreased with age (median OS: 21.6, 21.2, 17.0, and 13.9 months, respectively; p = 0.005). In patients aged < 75 years, independent prognostic factors identified by univariate and multivariate analyses included lymph node metastasis (hazard ratio [HR], 1.598; p = 0.007), tumor size (HR, 1.489; p = 0.043), R status (HR, 1.536; p = 0.011), and serum albumin levels (HR, 1.526; p = 0.031). In patients aged ≥ 75 years, a high modified frailty index (HR, 2.446; p = 0.012) emerged as an independent prognostic factor, along with lymph node metastasis, CA19‐9 level (HR, 1.897; p = 0.017), and R status (HR, 2.087; p = 0.007). Conclusion The prognosis for older patients with PDAC was shorter than that of younger patients. Frailty may contribute to their poorer prognosis in older age.